Androgenic response of Triticum durum-Dasypyrum villosum amphidiploids and their parental forms - H. Stoyanov; I. Belchev (Вавиловский журнал генетики и селекции)
Wide hybridization in cereal crops is one of the most efficient tools for the enrichment of genetic variability and addressing a number of breeding problems related to resistance and tolerance to biotic and abiotic stresses. Therefore, a large number of amphidiploids between species possessing different morphological, genetic and physiological properties have been developed. One of the most valuable species with regard to the possibilities for introducing valuable traits and properties into wheat species is the wild Dasypyrum villosum. With the aim to study the androgenic response of the Triticum durum-D. villosum amphidiploids, two accessions and their parental forms – the durum wheat cultivars Gergana and Argonavt and a landrace of the D. villosum – were studied. The following parameters were determined: callus induction, plant regeneration, yield of albino and green regenerants. It was found that the callus induction of the two studied amphidiploids differed significantly from that of the parental forms (2.1–7.2 %), being significantly higher, 30.7 and 16.5 %, respectively. Regardless of the difference in callus induction, the amphidiploids did not significantly differ from the parental forms in their regeneration ability. The yield of albino plants exceeded the yield of green regenerants and followed the tendency observed in callus induction. Green plants were found only in the amphidiploid Gergana-D. villosum and in the parental form durum wheat Gergana. Plants were regenerated from the species D. villosum, although they were only albinos, showing its good responsiveness to anther culture. The established characteristics of the amphidiploids and their parental forms make their practical use highly valuable for the improvement of different types of cereal crops.